2011
DOI: 10.1016/j.jacc.2011.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Ischemia-Causing Coronary Stenoses by Noninvasive Fractional Flow Reserve Computed From Coronary Computed Tomographic Angiograms

Abstract: Noninvasive FFR derived from CCTA is a novel method with high diagnostic performance for the detection and exclusion of coronary lesions that cause ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
366
2
17

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,113 publications
(390 citation statements)
references
References 34 publications
5
366
2
17
Order By: Relevance
“…Until 2014, adjunctive functional testing at this institution was performed by conventional MPI. Based on local pilot experiences together with published reports on the diagnostic performance of FFR CT testing4, 5, 6 and potential improvements in clinical workflows, we decided in 2014 to replace MPI with FFR CT for functional assessment of CAD determined by coronary CTA. At our institution, frontline MPI of patients with new‐onset chest pain without known CAD is recommended only for those with contraindications to coronary CTA 8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2014, adjunctive functional testing at this institution was performed by conventional MPI. Based on local pilot experiences together with published reports on the diagnostic performance of FFR CT testing4, 5, 6 and potential improvements in clinical workflows, we decided in 2014 to replace MPI with FFR CT for functional assessment of CAD determined by coronary CTA. At our institution, frontline MPI of patients with new‐onset chest pain without known CAD is recommended only for those with contraindications to coronary CTA 8.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these techniques, noninvasive fractional flow reserve (FFR) can be computed 3, 4, 5, 6. In studies including patients with known or suspected stable CAD and blinded comparison to FFR, coronary CTA‐derived FFR (FFR CT ) has shown high diagnostic performance 4, 5, 6. Recently, it was demonstrated in stable patients referred to ICA that initial FFR CT assessment reduced the downstream use of ICA procedures, the rate of ICA showing no obstructive CAD, and overall costs 7.…”
Section: Introductionmentioning
confidence: 99%
“…To further expand the use of physiological‐guided percutaneous coronary intervention, coronary computed tomography angiography– and invasive coronary angiography–based computation methods were developed for less‐invasive FFR approximation 4, 5, 6, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] A meta-analysis on three prospective multi-center FFRCT trials (NXT -Analysis of Coronary Blood Flow Using CT Angiography: Next Steps; DISCOVER-FLOW -Diagnosis of Ischemia-Causing Stenoses Obtained via Noninvasive Fractional Flow Reserve, and DeFACTODetermination of Fractional Flow Reserve by Anatomic Computed Tomographic Angiography) was recently published by Li et al, analyzing the diagnostic accurateness of FFRCT compared to invasively determined FFR (gold standard) and CCTA. The meta-analysis concluded that FFRCT demonstrated a high diagnostic capacity in determining coronary ischemia, with improved accuracy and specificity compared to CCTA.…”
Section: Accuracy Of Ffrctmentioning
confidence: 99%